2001
DOI: 10.1289/ehp.01109193
|View full text |Cite
|
Sign up to set email alerts
|

Paternal occupational exposures and childhood cancer.

Abstract: The objective of the study described here was to test the hypothesis that paternal occupational exposure near conception increases the risk of cancer in the offspring. We conducted a cohort study based on a population of 235,635 children born shortly after two different censuses in Sweden. The children were followed from birth to 14 years, and cases of cancer were identified in the Swedish Cancer Registry. Occupational hygienists assessed the probability of exposure to different agents in each combination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 30 publications
2
57
3
Order By: Relevance
“…Among these studies, 21 were excluded after reading of the full paper as they did not fulfil the inclusion criteria with regard to the outcome [19][20][21][22][23][24], or to the exposure [25][26][27][28][29][30][31][32][33][34][35] or to both [36] or to the population [37]. One cohort [38] and one case-control study [39] were also excluded because the data were redundant/updated/overlapped. The remaining 25 studies were included in present analyses.…”
Section: Literature Selection and Study Characteristicsmentioning
confidence: 99%
“…Among these studies, 21 were excluded after reading of the full paper as they did not fulfil the inclusion criteria with regard to the outcome [19][20][21][22][23][24], or to the exposure [25][26][27][28][29][30][31][32][33][34][35] or to both [36] or to the population [37]. One cohort [38] and one case-control study [39] were also excluded because the data were redundant/updated/overlapped. The remaining 25 studies were included in present analyses.…”
Section: Literature Selection and Study Characteristicsmentioning
confidence: 99%
“…The occupational exposure of a father just before conception is thought to increase the risk of cancer in his offspring through toxic inheritance (1). One of the causal mechanisms for such an association is thought to be that occupational exposure may bring about a genetic change in the father's sperm, which may ultimately affect the susceptibility of his children to cancer.…”
mentioning
confidence: 99%
“…In a study on several birth cohorts, Feychting et al (2001) found an increased risk of nervous system tumors related to paternal exposure to pesticides (RR 2.36; 1.27-4.39) and an increased risk of leukemia related to wood work (RR 2.18; 1.26-3.78). They found no association between childhood leukemia and paternal exposure to pesticides (RR 0.9; 0.37-2.19).…”
Section: Resultsmentioning
confidence: 99%
“…If, nevertheless, positive outcomes result from a variety of studies, this might well be interpreted as indicative of a very strong single causative factor, hidden among other exposures in the studies. However, it is hardly plausible to assume that a single carcinogen or a limited group of substances of such Associations not found ''All cancers'' Children of pesticides applicators (Flower et al 2004) Children of pesticides applicators (Rodvall et al 2003) Father's chlorophenate exposure (Heacock et al 2000) Paternal pesticide exposure (Fear et al 1998) Residence in area with high agricultural pesticide use Parental exposure to agrochemicals (McKinney et al 2003;Mutanen and Hemminki 2001) Leukemia Paternal wood work (Feychting et al 2001) Residence in area with high propargit use Use of pest control service after childbirth (Ma et al 2002) Use of pesticides during pregnancy (Ma et al 2002) Pesticide use on farm (Meinert et al 2000) Carbamates and MLL + (Alexander et al 2001) Indoor and garden use of insecticides, herbicides, ''products for trees, '' etc. (Infante-Rivard et al 1999) Father's chlorophenate exposure (Heacock et al 2000) Paternal pesticide exposure (Fear et al 1998;Feychting et al 2001) Pesticide use in garden or residential insecticide use (Meinert et al 2000) Carbamates and MML À (Alexander et al 2001) Flea control products …”
Section: Discussionmentioning
confidence: 99%